Acute and long-term effects of two different static stretching training protocols on range of motion and vertical jump in preadolescent athletes - Donti, O.; Papia, K.; Toubekis, A.; Donti, A.; Sands, W.; Bogdanis, G. (Biology of Sport, 2021)
This study examined the acute and long-term effects of two static stretching protocols of equal duration, performed either as a single stretch or multiple shorter duration repetitions on hip hyperextension range of motion (ROM) and single leg countermovement jump height (CMJ). Thirty female gymnasts were randomly assigned to stretching (SG) or control groups (CG). The SG performed two different protocols of static stretching, three times per week for 9 weeks. One leg performed repeated stretching (3 × 30 s with 30 s rest) while the other leg performed a single stretch (90 s). The CG continued regular training. ROM and CMJ were measured pre- and 2 min post-stretching on weeks 0, 3, 6, 9, and 3 weeks into detraining. CMJ height increased over time irrespective of group (main effect time, p = 0.001), with no statistical difference between groups (main effect group, p = 0.272). Three-way ANOVA showed that, CMJ height after stretching was not affected by either stretching protocol at any time point (p = 0.503 to 0.996). Both stretching protocols equally increased ROM on weeks 6 (10.9 ± 13.4%, p < 0.001, d = 0.42), and 9 (21.5 ± 13.4%, p < 0.001, d = 0.78), and this increase was maintained during detraining (17.0 ± 15.0%, p < 0.001, d = 0.68). No increase in ROM was observed in the CG (p > 0.874). Static stretching of long duration applied either as single or multiple bouts of equal duration, results in similar acute and long-term improvements in ROM. Furthermore, both stretching protocols do not acutely affect subsequent CMJ performance, and this effect is not influenced by the large increase in ROM and CMJ overtime.